A V-Cone meter measurement correlation in low pressure wet gas based on Chisholm model. (April 2019) - He, Denghui; Chen, Senlin; Bai, Bofeng
Abstract: To gain a deeper understanding of the performance of V-Cone meter in low pressure wet gas measurement, the over-reading of the V-Cone meter was experimentally investigated in the present study. The equivalent diameter ratio of the V-Cone meter is 0.55. The experimental fluids were air and tap water. The operating pressure and the gas volume fraction ranged from 0.1 MPa to 0.4 MPa and 97.52%–100%, respectively. The results showed that the existing V-Cone wet gas correlation, which was developed for the medium and high pressure wet gas cannot be well extended to the low pressure conditions. The Chisholm exponent monotonically decreased with the ratio of liquid-to-gas mass flow rate increasing, and was almost not affected by the gas to liquid density ratio and the gas densiometric Froude number in the present test ranges. A measurement correlation dedicated for the low pressure wet gas was developed. In the present cases, the relative deviation of the gas mass flow rate predicted by the new correlation was within ±4.0% and ±3.0% under the 95% and 90% confidence level, respectively; the average relative deviation was 0.046%. Our results provide insights into the measurement performance of V-Cone meter in low pressure wet gas and may help to develop a more comprehensive wet gas correlation. Graphical abstract: Fitting curve between m l /m g and n .Image 1 Highlights: V-Cone meter over-reading in low pressure wet gas measurement was investigated. Effects of parameters on Chisholm exponent were analyzed. A measurement correlation in low pressure wet gas was developed.